Aortocoronary graft flow and reactive hyperaemia in relation to postoperative myocardial infarction. Issue 2 (April 1976) - Skotnicki, S; Vonk, J; Sleegers, T; Dercksen, S; Linssen, G; Lacquet, L; Kuijpers, P
Abstract : Blood flow through aortocoronary venous grafts and its response to a brief period of arterial occlusion--reactive hyperaemia--were studied in relation to the development of postoperative myocardial infarction. In 40 patients with intractable angina due to obstructive coronary artery disease, 72 aortocoronary venous grafts were constructed. In 18% of the grafts there was no response to the flow to temporary occlusion, due to absence of reactive hyperaemia. In the remaining grafts the flow increased from 17% to 26%. In 17-5% of the patients postoperative myocardial infarction was diagnosed. No relation could be established between this control flow through aortocoronary grafts and postoperative myocardial infarction. A significant difference was found in the magnitude of the reactive hyperaemia following occlusion of the graft between patients who developed myocardial infarction (13-0%) and those who did not (26-8%). Some of our observations suggest that the myocardium is in a state of reactive hyperaemia after coronary surgery. With certain technical precautions the flow changes caused by reactive hyperaemia can be used as an indicator of the result to be expected from bypass surgery.